Developing models for communicative learning spaces - Yusof, Norhafezah; Abd Aziz, Fadzli Shah; Ahmad, Sa'ari; Hassan, Hamisah; Asmuni, Hishamuddin (Universiti Utara Malaysia, 2012)
The study aims to develop and create an electronic communicative space model for research type workplaces. This attempt is in line with the vision of the Malaysian government to develop Malaysia as an International Educational Hub for the Asian region. This attempt is drawn from Elsbach and Pratt’s suggestion (2007) that there is a gap to be filled by Asian researchers in studying spaces at workplaces through an integration of physical and social environment.The study employed a mixed method approach to realize space models for Higher Educational Institutions in Malaysia.This current study surveyed 222 respondents in three universities that have research centres.The results of the study demonstrated that the majority of the respondents preferred model number 5 based on the reconstruction of DEGW framework.Six experts were interviewed to provide guideline for space construction. The finding indicated four elements are needed in space construction namely, space requirement, space specificity, space and change and space design.Hence, space functionality and financial requirements are vital in designing communicative space models in higher learning institutions.This study contributes to the knowledge gap of space study from Asian perspective and assists in solving practical issues in space design for practitioners.